Canva Sebagai Media Interaktif dalam Pembelajaran Artikel Ilmiah Populer: Analisis Persepsi Siswa - Andhini, Putri; Fauziyyah, Sabrina; Nurjanah, Siti; Rozak, Abdul; Juwanda, Juwanda (SAWERIGADING, 2025)
This study aims to describe the perceptions of eighth-grade students regarding the use of the canva application as an interactive learning medium for popular scientific articles. The research employed a descriptive qualitative method, with data collected through questionnaires distributed to 32 students of class VIII G at MTs Negeri 4 Cirebon. The results indicate that students’ perceptions across four indicators—acceptance, understanding, evaluation, and reaction—are categorized as highly positive. Canva is considered effective in capturing attention, enhancing creativity, and fostering motivation and active participation. These findings align with Keller’s ARCS model, Mayer’s Cognitive Theory of Multimedia Learning, and Vygotsky’s Zone of Proximal Development. Overall, Canva is recommended as an innovative interactive learning medium that supports the development of students’ digital literacy in modern learning contexts.  AbstrakPenelitian ini bertujuan untuk mendeskripsikan persepsi siswa kelas VIII terhadap penggunaan aplikasi canva sebagai media pembelajaran interaktif pada materi artikel ilmiah populer. Metode yang digunakan adalah deskriptif kualitatif dengan pengumpulan data melalui kuesioner kepada 32 siswa kelas VIII G di MTs Negeri 4 Cirebon. Hasil penelitian menunjukkan bahwa persepsi siswa terhadap empat indikator—penerimaan, pemahaman, penilaian, dan reaksi berada pada kategori sangat positif. Aplikasi canva dinilai efektif dalam menarik perhatian, meningkatkan kreativitas, serta menumbuhkan motivasi dan partisipasi aktif siswa. Temuan ini sejalan dengan teori ARCS Keller, Cognitive Theory of Multimedia Learning Mayer, dan Zone of Proximal Development Vygotsky. Secara keseluruhan, canva dapat direkomendasikan sebagai media pembelajaran interaktif yang inovatif dan mendukung pengembangan literasi digital siswa dalam pembelajaran modern.